Hegemonic Antagonistism as An Emancipative Effort in Dickens's A Christmas Carol (1843): A Study of Laclau-Mouffe Post-Marxism - Muhammad Surahman Djunuhi (POETIKA, 2020)
This study aims to describe the dominant hegemony and antagonism or contestation of hegemony that occurred in the novel A Christmas Carol (1843) written by Charles Dickens. The method is descriptive qualitative with note-taking data collection techniques. The results of the study prove are (1) Scrooge, a banker who from the beginning was and acted egocentric, individualist, and likes to exploit his employee, is the representation of the dominant capitalist hegemony. This domination has become the enemy and triggered the existence of humanist religiosity, counter-hegemony, or the people which are a hegemony collaboration of discourses of anti-exploitation, anti-discrimination, anti-egocentrism, and anti-individualism represented through social order and figures around Scrooge. (2) Scrooge's identity and ideology which is dominated by Capitalism hegemony are not full and dynamic. The lack of identity fullness gives a possibility to the transformation of identity and ideology in Scrooge. This is reinforced by the presence of antagonism of dominant hegemony, capitalism, and counter-hegemony, humanist religiosity that has implications for changing the attitude of Scrooge to become a rich person who is generous, religious, friendly, humanist, anti-exploitative, and anti-individual. Thus, the figure of Scrooge has become the arena of antagonism of hegemony in which the presence of hegemonic antagonism is an emancipatory effort countering and undermining the dominance of capitalism.